Siderophore production: A unique quality of pathogenic Klebsiella pneumonia to survive in low iron concentration (Asian Journal of Medical and Biological Research, 2015)
Klebsiella pneumonia is the second most causing agent of urinary tract bacterial infection among human beings. Its ability to grow and to produce siderophores is dependent on the iron content and the type of carbon sources in the culture medium. This study has aimed to find out the unique properties of siderophore production by Klebsiella species in fluctuating iron concentrations. The study was carried out on 252 urine samples collected from UTI patients at Doon (PG) Paramedical College and Teaching Hospital, Dehradun, India. All urine samples were tested microbiologically using standard procedure and biochemical panel tests were performed to identify and to isolate Klebsiella pneumonia from colonies obtained on differential media plate used for urine culture and the result was interpreted according to National Committee for Clinical Laboratory Standards (NCCLS) guide line to confirm the Klebsiella pneumonia. Then CAS siderophore detection method was applied to quantify the siderophore production in various iron concentration supplied to culture medium. A total of 47 patients out of 252 UTI patients were found to be infected by Klebsiella pneumonia. Women were more prone to be UTI infected by Klebsiella pneumonia in comparison to men (14.89% men, 85.1% women). Most of the UTI patients infected by Klebsiella pneumonia were in the age group of 50-79 years (53.19%) which was followed by 20-49 years (23.40%) and 80-99 years (14.89%) respectively. Least people having age below 19 years old were prone to be urinary tract infected by Klebsiella pneumonia. In the same way, siderophore production was found to be increased significantly when there was no iron in the culture medium and its production was decreased gradually with increase in iron concentration up to 200mg/L in the culture medium. Siderophore is an important metabolite product for pathogenic Klebsiella pneumonia to survive and cause pathogenicity in low iron concentration medium.Asian J. Med. Biol. Res. June 2015, 1(1): 130-138